مطالعہ یہودیت میں مسلم مفکرین کے مناھج: قرآنی و حدیثی تناظرات اور مختلف آراء کا تجزیاتی مطالعہ: Approaches of Muslim Thinkers in the Study of Judaism: Analytical Examination of Qur’anic and Hadith Correspondences and Various Perspectives - Tahir, Noreen; Yousaf, Umer; Sajid, Dr. Muhammad Tufail (Al-Amīr Research Journal for Islamic Studies, 2024)
The study explores the methodologies employed by Muslim intellectuals in examining Judaism, focusing on Quranic and Hadith references and diverse viewpoints. This analytical inquiry delves into the comparative analysis of Islamic and Judaic teachings, shedding light on the intersections and divergences between the two faiths. By examining various perspectives, the study aims to provide insights into the nuanced approaches adopted by Muslim thinkers in understanding Judaism, thereby contributing to interfaith dialogue and scholarly discourse. Keywords: Muslim thinkers, Judaism, Quranic references, Hadith, comparative analysis, interfaith dialogue, scholarly discourse.